2005
DOI: 10.1063/1.1856225
|View full text |Cite
|
Sign up to set email alerts
|

Magnetization dependence on electron density in epitaxial ZnO thin films codoped with Mn and Sn

Abstract: The magnetic and transport properties of Mn-doped ZnO thin films codoped with Sn are examined. Superconducting quantum interference device magnetometry measurements indicate that the films are ferromagnetic with an inverse correlation between magnetization and electron density as controlled by Sn doping. Magnetism in low free-electron density material is consistent with the bound magnetic polaron model, in which bound acceptors mediate the ferromagnetic ordering. Increasing the electron density decreases the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(32 citation statements)
references
References 55 publications
2
30
0
Order By: Relevance
“…That is to say, not all the stoichiometric Mn 2+ has entered the ZnO lattice, the rest of Mn 2+ has been oxidized into manganese oxide. Ivill et al [24] has also reported the precipitation of Mn 3 O 4 in Zn 1−x Mn x O powder deposited on sapphire by pulsed laser deposition (PLD) at the Mn concentration of 3 at%. Samples were randomly orientated along different planes, the "d" value were compared with standard JCPDS data card (79-0207) which confirms the wurtzite structure of the materials.…”
Section: Morphological and Structural Propertiesmentioning
confidence: 99%
“…That is to say, not all the stoichiometric Mn 2+ has entered the ZnO lattice, the rest of Mn 2+ has been oxidized into manganese oxide. Ivill et al [24] has also reported the precipitation of Mn 3 O 4 in Zn 1−x Mn x O powder deposited on sapphire by pulsed laser deposition (PLD) at the Mn concentration of 3 at%. Samples were randomly orientated along different planes, the "d" value were compared with standard JCPDS data card (79-0207) which confirms the wurtzite structure of the materials.…”
Section: Morphological and Structural Propertiesmentioning
confidence: 99%
“…The (Ga,Mn)As is regarded as a classic example with robust ferromagnetism [1], but the highest reported T c 's are still well below room temperature [2,3]. Alternatively, p-type (Zn,Mn)O has been predicted to be a room temperature ferromagnet [4,5], where ferromagnetism above room temperature has been observed for Mn doped pure ZnO [6,7,8], or Mn doped p-type ZnO [9,10,11,12,13]. However, contradictory experimental results have also been reported for (Zn,Mn)O such as ferromagnetism below room temperature [14], absence of ferromagnetism [15], spin glass behavior [16], or paramagnetism [17].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Mn 2+ : ZnO has been reported to be paramagnetic at all temperatures [8][9][10] and ferromagnetic with T C below 11,12 or above room temperature [13][14][15][16] and to show high-T C ferromagnetism with n-type 17,18 or p-type conductivity. [13][14][15]19 There have also been several recent reports of ferromagnetism in Mn 2+ : ZnO having origins extrinsic to the DMS ͑e.g., Zn-doped manganese oxide precipitates͒.…”
Section: Resultsmentioning
confidence: 99%
“…3͑a͔͒. 18 The increased electron density was argued to quench the holes mediating ferromagnetic ordering of Mn 2+ moments. Venkatesan et al found that increasing the concentration of n-type defects ͑by decreasing the O 2 partial pressure during growth, which increases the concentration of oxygen vacancies V O 2− and interstitial zinc Zn i ͒ led to larger saturation moments in ferromagnetic Co 2+ : ZnO with constant Co 2+ concentration ͓Fig.…”
Section: A Magnetic Properties Of Comentioning
confidence: 99%